Impact of high-intensity polio eradication activities on children’s routine immunisation status in Northern India - Haenssgen, M (Oxford University Press, 2017)
regression, controlling for other determinants of immunisation. The regression results show that the link is negative in Uttar Pradesh and positive in Bihar. Age-specific analysis shows that the positive association diminishes for older children in Bihar and that a negative association emerges and become increasingly pronounced for older children in Uttar Pradesh. This indicates that heterogeneous results emerge across two neighbouring states with similar programme intensity and suggests that the catch-up of unvaccinated older children may be a channel through which negative effects accrue. The method described in this paper, based on an analytical focus on individual-level programme exposure, can therefore help health policy implementers and evaluators to illuminate positive or negative interactions between a health intervention and a health system.